Perbandingan Penggunaan System Usability Scale dan Usefull, Satisfaction and Ease of Use Questionnaire pada Usability Testing - Sifa Amalia Purnamasari; Nono Heryana; Kamal Prihandani (Department of Science and Technology Ibrahimy University, 2021)
Since the emergence of the Covid-19 virus in Indonesia, learning activities in the education system have been changed to distance learning using online media. The most widely used application according to the results of interviews with teacher representatives from 4 vocational schools in Karawang Regency is Google Classroom. However, the application received a poor rating based on the rating on the Google Play Store. So that usability testing is carried out in order to assess the effectiveness, efficiency and user satisfaction of the application. There are several usability testing techniques, including (SUS) System Usability Scale and Usefull, Satisfaction and ease of Use (USE) Questionnaire. This study aims to obtain the results of usability testing and a comparison between the two techniques used. Both have some similarities where the analysis can be done using any media, it's just that there are differences in the number of questions and data analysis. The System Usability Scale (SUS) technique contains 10 questions while the Usefull, Satisfaction and ease of Use (USE) Questionnaire technique contains 30 questions with 3 main dimensions, namely Usefulness, Satisfaction and Ease of Use. The research method used is Product Moment Pearson’s method for data validity analysis and Cronbbach's Alpha method for data reliability analysis. This research is a quantitative descriptive study conducted on 50 high school students/equivalent and university students. The results of the questionnaire technique (SUS) System Usability Scale state that Google Classroom has a good interface with a score of 72 with advantages in ease of use and desire to use it again, while based on the Usefull, Satisfaction and ease of Use (USE) Questionnaire technique states Google Classroom has an average value of 84% with 81% (usefulness), 86% (ease of use), 87% (ease of learning) and 83% (satisfaction). Then according to the comparison, the Usefull, Satisfaction and ease of Use (USE) Questionnaire technique is stated to be better with a reliability value of 0.967 while (SUS) System Usability Scale only has reliability (0.634).